Popularity in Social Networks. The Case of Argentine Beekeeping Production Entities - Andrieu, Jimena; Fernández-Uclés, Domingo; Mozas-Moral, Adoración; Bernal-Jurado, Enrique (MDPI, 2022)
The context of the COVID pandemic has accelerated the pace of the digitalization of society, especially of its business fabric. Among the various applications offered by the Internet, social networking platforms have been identified as powerful tools that organizations have at their disposal for the development of their online business activities. This is due to the closeness and trust generated by word-of-mouth communication. In this context, the aim of this article is to identify which organizational characteristics are directly related to popularity on social networks, measured by the number of followers on these accounts. In order to achieve this objective, the Argentinean beekeeping organizations have been taken as a case study and the fuzzy set Qualitative Comparative Analysis method has been used. The results obtained allow us to validate the different organizational factors which, beyond the use of Facebook itself, lead to better results for the organizations in their social network strategies. These factors include their cooperative nature, localization, environmental sensitivity and presence on other digital platforms.